The Relationship of Risk Factors on Quality of Life of Laryngeal Carcinoma Patients after Chemoradiation at Kariadi General Hospital - Albert Juneson; Willy Yusmawan; Kanti Yunika; RR Lydia Purna Widyastuti Setjadiningrat Kuntjoro (Jurnal Kedokteran Diponegoro (Diponegoro Medical Journal), 2024)
Background: Laryngeal carcinoma is a carcinoma that forms in the tissue of the larynx. The cause of laryngeal carcinoma is not known with certainty, but many risk factors can cause laryngeal carcinomas, such as a history of smoking, alcohol consumption, gender, age, and exposure environment. The quality of life of patients with laryngeal carcinoma after chemoradiation can be influenced by several things, including several risk factors for laryngeal carcinoma. Objective: The purpose of this study was to assess the association of risk factors with the quality of life of laryngeal carcinoma patients after chemoradiation at Kariadi General Hospital. Methods: This study is a cross-sectional study with samples of laryngeal carcinoma patients who have received chemoradiation therapy at Kariadi General Hospital. Sampling was carried out using a consecutive sampling technique using a Univesity of Washington Quality of Life (UW-QoL) questionnaire which was translated into Bahasa. The data from the sampling was then processed using the IBM SPSS Statistics 25.0 application. Results: Overall, the quality of life of laryngeal carcinoma patients after chemoradiation was categorized as “good” quality of life with a mean score of 62. There was no significant relationship (p<0.05) between the quality of life scores and each risk factor for laryngeal carcinoma. Conclusion: There is no significant relationship between risk factors on the quality of life of laryngeal carcinoma patients after chemoradiation at Kariadi General Hospital.